Review of designs of machines for surface compaction of products made of construction mixtures - POCHKA, Kostiantyn; ZAICHENKO, Stefan; SHALENKO, Vadym; MASLIUK, Andrii; BARYLIUK, Maksym; BARYLIUK, Serhii (Ways to Improve Construction Efficiency, 2024)
Concrete works are the most important in construction by scope and cost. Concrete as a building material serves as the basis for creating load-bearing structures of buildings and constructions. This is justified by its high mechanical characteristics and processability. Almost any construction elements of structures of any configuration and purpose can be made of concrete. This research conducted a comprehensive analysis of surface-acting molding equipment of construction industry plants – vibrating and non-vibrating. The surface-acting molding equipment using vibratory action on the mixture to be compacted is considered. Examples of such installations are locally developed and self-propelled plates of foreign companies Dynapas and Amman. The use of pendulum vibration exciters in autonomous vibrating compactors makes it possible to obtain directional vibrations. The versatility of Amman vibrating plates is ensured by changing the direction of the vibration speed, used for trenches and large areas, and has a working width adjustment. ZENIT-TECHNO is also engaged in the production of equipment for the concrete industry, which presents a wide range of equipment for the production of concrete mixtures – lines for the production of concrete products by vibration under pressure, molds for any products, installations for processing concrete products, equipment and tools for laying paving stones, slabs, curbs, and various clamps. Despite the continuous improvement of vibratory concrete forming units, it is still impossible to get rid of the increased noise and vibration levels at workplaces, which creates harmful working conditions. Non-vibration forming methods not only eliminate the disadvantages of vibration technology, but also open up new opportunities to increase labor productivity and reduce the metal consumption of equipment. One of the methods of non-vibration molding is roller pressing, which is characterized by the fact that new portions of the mixture are repeatedly pressed into the freshly laid layer under the roller, which reciprocates across the mold. Extrusion pressing involves pushing the raw material mass through a hole in the die with a screw. The analysis of existing technical and economical information, experience of industrial and laboratory researches suggests that the calculation, design and creation of new concrete forming units are relevant and promising at the present stage of their use.